Cerebrospinal fluid penetration of fosfomycin in patients with ventriculitis: an observational study - Christina König; Jens Martens-Lobenhoffer; Patrick Czorlich; Manfred Westphal; Stefanie M. Bode-Böger; Stefan Kluge; Jörn Grensemann (BMC, 2023)
Abstract Background For treatment of ventriculitis, vancomycin and meropenem are frequently used as empiric treatment but cerebrospinal fluid (CSF) penetration is highly variable and may result in subtherapeutic concentrations. Fosfomycin has been suggested for combination antibiotic therapy, but data are sparse, so far. Therefore, we studied CSF penetration of fosfomycin in ventriculitis. Methods Adult patients receiving a continuous infusion of fosfomycin (1 g/h) for the treatment of ventriculitis were included. Routine therapeutic drug monitoring (TDM) of fosfomycin in serum and CSF was performed with subsequent dose adaptions. Demographic and routine laboratory data including serum and CSF concentrations for fosfomycin were collected. Antibiotic CSF penetration ratio as well as basic pharmacokinetic parameters were investigated. Results Seventeen patients with 43 CSF/serum pairs were included. Median fosfomycin serum concentration was 200 [159-289] mg/L and the CSF concentration 99 [66-144] mg/L. Considering only the first measurements in each patient before a possible dose adaption, serum and CSF concentrations were 209 [163-438] mg/L and 104 [65-269] mg/L. Median CSF penetration was 46 [36-59]% resulting in 98% of CSF levels above the susceptibility breakpoint of 32 mg/L. Conclusion Penetration of fosfomycin into the CSF is high, reliably leading to appropriate concentrations for the treatment of gram positive and negative bacteria. Moreover, continuous administration of fosfomycin appears to be a reasonable approach for antibiotic combination therapy in patients suffering from ventriculitis. Further studies are needed to evaluate the impact on outcome parameters.